Liberdade e tolerância em John Stuart Mill : uma análise a partir de Isaiah Berlin, Alex Zakaras e George Fletcher - Santos, Giovane Martins Vaz dos (2021)
This work aims to analyze the John Stuart Mill’s concept of toleration from three philosophers who interpret the millian’s liberalism: Isaiah Berlin, Alex Zakaras and George P. Fletcher. The investigation starts from the follow problem: how the millian’s concept of toleration is analyzed by I. Berlin, A. Zakaras and G. Fletcher? With this delimitation we pretended to analyze the concept of toleration from three aspects: 1) the relation between liberty and toleration; 2) the pluralist interpretation of J. S. Mill; 3) the conceptual limits of J. S. Mill’s notion of toleration. The work is divided in two parts: firstly, the concept of toleration is presented from the justification of the utilitarianism and of the civil liberties. Thus, the first part is divided in two chapters: in the first we analyze the utilitarian justification of the concept of toleration, in which the millian’s concept of human nature and the philosopher’s analysis of the tyranny of majority are explored. In the second chapter, the harm principle and the duty of official intervention are investigated in the face of the Mill’s concept of toleration. In the second part, the John Stuart Mill’s concept of toleration is analyzed from Isaiah Berlin, Alex Zakaras and George P. Fletcher. Berlin and Zakaras analyzed two central aspects of Mill’s liberalism: negative liberty and value pluralism. Fletcher, in its turn, makes a reflection on the instability of toleration. The analysis of the three authors helps to expand the comprehension of the millian’s notion of toleration and, at the same time, to delimitate the thought of the English philosopher, contributing to the update of the topic in the contemporary debates about toleration in Political Philosophy and Philosophy of Law.